Visible-light promoted catalytic activity of dumbbell-like Au nanorods supported on graphene/TiO2 sheets towards hydrogenation reaction. (13th April 2018) - Dai, Yunqian; Zhu, Mingyun; Wang, Xiaotian; Wu, Yanan; Huang, Chengqian; Fu, Wanlin; Meng, Xiangyu; Sun, Yueming
Abstract: In this work, the rationally-designed sharp corners on Au nanorods tremendously improved the catalytic activity, particularly in the presence of visible light irradiation, towards the hydrogenation of 4-nitrophenol to 4-aminophenol. A strikingly increased rate constant of 50.6 g −1 s −1 L was achieved in M-Au-3, which was 41.8 times higher than that of parent Au nanorods under dark conditions. The enhanced activities were proportional to the extent of the protruding sharp corners. Furthermore, remarkably enhanced activities were achieved in novel ternary Au/RGO/TiO2 sheets, which were endowed with a 52.0 times higher rate constant than that of straight Au nanorods. These remarkably enhanced activities were even higher than those of previously reported 3–5 nm Au and 3 nm Pt nanoparticles. It was systematically observed that there are three aspects to the synergistic effects between Au and RGO sheets: (i) electron transfer from RGO to Au, (ii) a high concentration of p -nitrophenol close to dumbbell-like Au nanorods on RGO sheets, and (iii) increased local reaction temperature from the photothermal effect of both dumbbell-like Au nanorods and RGO sheets.